2007
DOI: 10.1159/000111142
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Reverses High Glucose-Induced Apoptosis of Mesangial Cells via Modulation of Wnt Signaling Pathway

Abstract: Background/Aims: Disruption of Wnt/β-catenin signaling in mesangial cells is a pathogenic consequence of diabetic nephropathy. We examined the role of simvastatin (SIM) in modulation of Wnt/β-catenin signaling in the apoptosis of high glucose (HG)-stressed mesangial cells in vitro and in vivo. Methods: For in vitro studies, we cultured mesangial cells, with or without SIM pretreatment, in 35 mM glucose and then assayed Wnt activity and apoptosis. For in vivo studies, we administered SIM to streptozocin-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…In addition, transfection of MCs with Wnt4, Wnt5a or persistent activation of β-catenin, was able to inhibit high glucose-induced mesangial apoptosis. Furthermore, treatment with simvastatin restored Wnt4, Wnt5a and β-catenin expression in MCs and attenuated diabetic kidney injuries both in vivo and in vitro (16). In addition, it has been demonstrated that abrogation of oxidative stress may restore Wnt5a/β-catenin signaling and attenuate high glucose-induced MC apoptosis (25).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, transfection of MCs with Wnt4, Wnt5a or persistent activation of β-catenin, was able to inhibit high glucose-induced mesangial apoptosis. Furthermore, treatment with simvastatin restored Wnt4, Wnt5a and β-catenin expression in MCs and attenuated diabetic kidney injuries both in vivo and in vitro (16). In addition, it has been demonstrated that abrogation of oxidative stress may restore Wnt5a/β-catenin signaling and attenuate high glucose-induced MC apoptosis (25).…”
Section: Discussionmentioning
confidence: 95%
“…In podocyte injury and proteinuric kidney diseases, the Wnt pathways are essential regulators and potential therapeutic targets (13,14). Studies regarding the role of the Wnt signaling pathway in MCs have mainly focused on hyperglycemic conditions (15,16,25,26). Lin et al (15) observed that in diabetic nephropathy, the Wnt/β-catenin signaling pathway serves a crucial role in the regulation of MC proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMCs are exposed to non-physiological doses of glucose in PD patients. Generally, PDFs contain high concentrations of glucose as an osmotic substance, and high glucose concentrations are known to influence cell survival, growth and apoptosis, and affect cell signaling pathways in several cell types [13,26]. Although the effects of high glucose concentrations on cell survival and morphological changes in PMCs have been reported [14], the molecular mechanisms and cell signaling pathways are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…They also decrease renal inflammatory diseases through molecular pathways and declining oxidative stress [8] and the urinary stone formation [9]. They are introduced to improve the renal function particularly in spinal injuries to prevent urinary complication [10].…”
Section: Introductionmentioning
confidence: 99%